Smoking in Relation to Age in Aesthetic Facial Surgery - Deliaert, An E. K. (Springer-Verlag, 2012)
BACKGROUND: Smoking is a major cause of premature facial aging. Skin aging in general, often accompanied by wrinkling and furrowing, plays a significant role in the decision to undergo aesthetic surgery. Smoking may therefore be related to the demand for cosmetic surgery. This study aimed to compare smoking habits with respect to a standard cosmetic procedure (blepharoplasty) in the general population and to evaluate whether the age at surgery differs between smokers and nonsmokers. METHODS: A questionnaire was sent to 517 patients with valid reports describing dermatochalasis of the upper eyelid who subsequently underwent an upper-eyelid correction in 2004. Smoking habits, socioeconomic status, and medical history were evaluated. The patients were classified as smokers, ex-smokers with at least 1 year of smoking cessation, and never-smokers. RESULTS: Of the 353 questionnaires (68.3 %) returned, 345 were eligible for statistical analysis. The smoking habits did not differ between the blepharoplasty group and the general population. However, the smokers underwent surgery an average of 3.7 years earlier than the ex-smokers (p = 0.0007) and 3.5 years earlier than the never-smokers (p = 0.006). No significant difference was observed between the ex-smokers and the never-smokers. CONCLUSIONS: This is the first study to describe an association between smoking habits and an earlier need for upper-eyelid correction among ex- and never-smokers. The mechanism of skin restoration could result in a regenerative mechanism among ex-smokers, but further research is needed to support this hypothesis. LEVEL OF EVIDENCE III: This journal requires that authors assign a level of evidence to each article. For a full description of these Evidence-Based Medicine ratings, please refer to the Table of Contents or the online Instructions to Authors at www.springer.com/00266.